Solo Travel and Well-Being Amongst Women: An Exploratory Study - Sheeba Hamid; Ruksar Ali; Mohd. Azhar; Sujood Khan (Lasigo Akademia Indonesia, 2021)
Solo travel is no longer a niche market. It alone contributes a massive amount of the total travel market and has shown an enormous growth in recent years. But the existing body of literature on solo women travelling and its outcomes is quite negligible. Consequent upon the fact, this study significantly contributes in the increment of existing literature. A conceptual model is proposed based on the secondary data sources and presents a discussion on the impact of solo travel experiences on women’s well-being. For this purpose, a range of research papers, articles, blogs and other relevant social media contents have been reviewed to draw conclusive results for the study. In the findings, self-transformation and positive changes in well-being came out as resultant factors of solo travelling in many cases. Major reasons for solo travelling found during the study were—to overcome stress and depression, to bring positive change in present state of life, escape, happiness, empowerment, self-growth and self-realisation. This paper significantly adds to further researches on women solo travelling trends by providing insights into independent form of travel and draws attention towards its importance for women’s health.